The Importance of the National Parks Model in the Development of International Ecotourism in New Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In the article, scientific and practical proposals and recommendations are developed on the importance of ecotourism resources in the development of international ecotourism in New Uzbekistan.